2013
DOI: 10.1017/s1368980013002516
|View full text |Cite
|
Sign up to set email alerts
|

Examining local-level factors shaping school nutrition policy implementation in Ontario, Canada

Abstract: Objective: Increasing numbers of overweight and obese youth draw attention to the school as an important setting for targeted nutrition interventions, given that it is where they spend a majority of their waking time. The objective of the present study was to explore local-level factors shaping the implementation of a school nutrition policy. Design: In-depth, semi-structured interviews were conducted in person or via the telephone (a maximum of 60 min). An interview guide was informed by the Analysis Grid for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 33 publications
5
71
2
1
Order By: Relevance
“…10 Preliminary studies indicate that some school stakeholders have encountered difficulties implementing P/PM 150, thereby limiting the ability of schools to reach full policy compliance. [11][12][13] These findings are consistent with reports that nutrition policy adherence typically takes years. 14,15 Policies can falter when the local context is unsupportive of the change (e.g.…”
Section: Introductionsupporting
confidence: 90%
“…10 Preliminary studies indicate that some school stakeholders have encountered difficulties implementing P/PM 150, thereby limiting the ability of schools to reach full policy compliance. [11][12][13] These findings are consistent with reports that nutrition policy adherence typically takes years. 14,15 Policies can falter when the local context is unsupportive of the change (e.g.…”
Section: Introductionsupporting
confidence: 90%
“…The removal of such products demonstrates that schools have made progress, though research has indicated that it can take months to years to improve the nutritional quality of products offered for sale in vending machines. 9,16,22,23 The ability to make and sustain changes also requires ongoing support, a weakness identified in all evaluations of P/PM 150. 18,19 The Ontario Ministry of Education-mandated P/PM 150 entrusted dissemination to regional school boards and left implementation to schools.…”
Section: Vending Products Versus Nutrition Standardsmentioning
confidence: 99%
“…16,17 Studies to date, though valuable, have not clearly identified the types of beverages or snacks that are non-compliant, nor conducted an audit of school vending machines in Ontario secondary schools. Furthermore, compliance, which typically takes years to achieve successfully, has not been tracked over time.…”
mentioning
confidence: 99%
“…Although actions to increase access to fresh and healthy foods (e.g. healthy corner store interventions) are recognized elements shaping food environments, [13][14][15][16] and although formal food safety activities (e.g. licensing, inspection) have recently been noted as policy tools with which to improve food environments, 17 studies that explicitly explore food safety and foodborne disease risk as part of healthy food environments in Canada are lacking.…”
Section: Introductionmentioning
confidence: 99%